Renewable Energy in Uzbekistan - Abduvaliyev Muhammadsodiq Qamardin o‘g‘li (Research Parks Publishers, 2021)
Renewable energy is derived from natural processes that are replenished constantly. Included in the definition is electricity and heat generated from solar, wind, ocean, hydropower, biomass, geothermal resources, and biofuels and hydrogen derived from renewable resources. The article discusses the sources of renewable energy in Uzbekistan.